Delivery of Cinnamic Aldehyde Antioxidant Response Activating nanoParticles (ARAPas) for Vascular Applications - Ana E. Cartaya; Halle Lutz; Sophie Maiocchi; Morgan Nalesnik; Edward M. Bahnson (MDPI AG, 2021)
Selective delivery of nuclear factor erythroid 2-related factor 2 (Nrf2) activators to the injured vasculature at the time of vascular surgical intervention has the potential to attenuate oxidative stress and decrease vascular smooth muscle cell (VSMC) hyperproliferation and migration towards the inner vessel wall. To this end, we developed a nanoformulation of cinnamic aldehyde (CA), termed Antioxidant Response Activating nanoParticles (ARAPas), that can be readily loaded into macrophages ex vivo. The CA-ARAPas-macrophage system was used to study the effects of CA on VSMC in culture. CA was encapsulated into a pluronic micelle that was readily loaded into both murine and human macrophages. CA-ARAPas inhibits VSMC proliferation and migration, and activates Nrf2. Macrophage-mediated transfer of CA-ARAPas to VSMC is evident after 12 h, and Nrf2 activation is apparent after 24 h. This is the first report, to the best of our knowledge, of CA encapsulation in pluronic micelles for macrophage-mediated delivery studies. The results of this study highlight the feasibility of CA encapsulation and subsequent macrophage uptake for delivery of cargo into other pertinent cells, such as VSMC.